2021
DOI: 10.1167/iovs.62.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the White-to-White Distance in 39,986 Chinese Cataractous Eyes

Abstract: PURPOSE.To investigate the distribution of white-to-white (WTW) distance and its associations with other biometric parameters in Chinese cataractous eyes. METHODS.Data on 39,986 eyes from 23,627 Chinese cataract patients were analyzed. Ocular biometric parameters, including WTW distance, corneal curvature, anterior chamber depth (ACD), lens thickness (LT), central corneal thickness (CCT), and axial length (AL), were obtained using the ZEISS IOLMaster 700. RESULTS.The mean age of patients was 63.7 ± 12.4 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
8
20
2
Order By: Relevance
“…While in Wei et al's study the participants were cataractous patients aged 63.7 ± 12.4 years, our study population was young myopic adults with a mean age of 25.14 ± 5.41 years. Different from our study, the WTW and ACD in Wei et al's study, might be affected by older age and the cataract ( 14 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…While in Wei et al's study the participants were cataractous patients aged 63.7 ± 12.4 years, our study population was young myopic adults with a mean age of 25.14 ± 5.41 years. Different from our study, the WTW and ACD in Wei et al's study, might be affected by older age and the cataract ( 14 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Precise preoperative WTW and ACD measurement are significantly associated with accurate IOL positioning after cataract surgery, which is one of the important factors related to satisfactory postoperative visual outcomes ( 8 , 9 , 29 ). In a recent study, larger WTW was observed in younger male patients and eyes with flatter corneas, deeper anterior chambers, thicker lenses, and thinner central corneal thickness ( 14 ). The largest WTW was found in eyes with axial length of 24.5 to 26 mm ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might indicate that a smaller cornea or a longer axis is more likely to exhibit a higher astigmatism. Similar patterns were confirmed by a recent study in 39,986 Chinese cataractous eyes 26 . Further study should be performed to clarify the relationships between corneal astigmatism and other ocular characteristics.…”
Section: Discussionsupporting
confidence: 91%